STREAM CIPHER ALGORITHM FOR ENCRYPTING TEXT USING LOGISTIC MAP, AUTO PARAMETERS LINEAR CONGRUENTIAL GENERATOR (APLCG), AND GRAY CODE - Fanggidae, Adriana; Polly, Yulianto Triwahyuadi; Sina, Derwin Rony; Letelay, Kornelis; Nabuasa, Yelly Yosiana; Boru, Meiton; Ledoh, Juan Rizky Mannuel (Informatika, Universitas Jenderal Soedirman, 2024)
One aspect frequently posing a challenge in cryptography pertains to the length of the secret key that users must remember. Achieving the requisite key length for cryptographic algorithms necessitates key padding. However, it is crucial to note that key padding is susceptible to predictable patterns. Both the Linear Congruential Generator (LCG) and gray code are algorithms employed to generate sequences of padded key bits. Regrettably, LCG requires the determination of two pre-defined parameters, whereas the Auto Parameters Linear Congruential Generator (APLCG) automatically establishes these parameters. These parameters play a pivotal role in generating unique sequences of random integers. To fortify key security, the generation of new keys is performed using a modified logistic map, an enhancement of the standard logistic map that exhibits random behavior consistently. Stream cipher, an encryption algorithm, necessitates a continuous key stream matching the bit or byte length of the message. We conducted experiments on stream cipher algorithms employing key streams generated from APLCG, gray code, and modified logistic map. Twenty text documents were utilized as test samples. The outcomes indicate that stream ciphers employing APLCG, gray code, and modified logistic map demonstrate high-security performance based on the statistical analysis conducted.